Graphdiyne oxide nanosheets display selective anti-leukemia efficacy against DNMT3A-mutant AML cells - Wang, Qiwei; Liu, Ying; Wang, Hui; Jiang, Penglei; Qian, Wenchang; You, Min; Han, Yingli; Zeng, Xin; Li, Jinxin; Lu, Huan; Jiang, Lingli; Zhu, Meng; et al. (Nature communications, 2022)
DNA methyltransferase 3 A ( DNMT3A ) is the most frequently mutated gene in acute myeloid leukemia (AML). Although chemotherapy agents have improved outcomes for DNMT3A -mutant AML patients, there is still no targeted therapy highlighting the need for further study of how DNMT3A mutations affect AML phenotype. Here, we demonstrate that cell adhesion-related genes are predominantly enriched in DNMT3A -mutant AML cells and identify that graphdiyne oxide (GDYO) display an anti-leukemia effect specifically against these mutated cells. Mechanistically, GDYO directly interacts with integrin β2 (ITGB2) and c-type mannose receptor (MRC2), which facilitate the attachment and cellular uptake of GDYO. Furthermore, GDYO binds to actin and prevents actin polymerization, thus disrupting the actin cytoskeleton and eventually leading to cell apoptosis. Finally, we validate the in vivo safety and therapeutic potential of GDYO against DNMT3A -mutant AML cells. Collectively, these findings demonstrate that GDYO is an efficient and specific drug candidate against DNMT3A -mutant AML. DNA methyltransferase 3A, a mutated gene associated with hematologic malignancies in age-related clonal haematopoiesis lacks targeted therapies. Here, the authors screen carbon nanomaterials and find graphdiyne oxide binds to mutant cells and disrupts cellular processes with a therapeutic effect in vitro and in vivo.